The unique Akt inhibitor SC66 suppressed AMPK activity and abolished autophagy through the EGFR‐p62 pathway. (9th December 2021) - Hou, Bolin; Li, Erwei; Liang, Jingnan; Liu, Shuchun; Yang, Huaiyi; Liu, Ling; Jiang, Xuejun
Abstract: Akt is usually considered to be a negative regulator of both autophagy and adenosine 5′‐monophosphate (AMP)‐activated protein kinase (AMPK) signaling. In the present study, we found that SC66, a pyridine‐based allosteric Akt inhibitor, suppressed basal and H2 O2 ‐induced autophagy concurrent with decreased phosphorylation and activity of AMPK. SC66 treatment led to the formation of a high molecular weight (HMW) form of SQSTM1/p62 (p62), which is an autophagic substrate and is essential for selective autophagy. Moreover, we observed that SC66 inhibited the binding of p62 and microtubule‐associated protein light chain 3 (LC3). The immunoprecipitation results revealed the interaction between p62 and epidermal growth factor receptor (EGFR), and knockdown of EGFR reversed SC66‐mediated autophagy inhibition without affecting the phosphorylation of acetyl‐CoA carboxylase (ACC), a well‐known substrate of AMPK. SC66 increased the interaction between EGFR and Beclin 1 and markedly decreased the association of EGFR with VPS34, a critical protein for autophagy induction. Collectively, the data presented here indicate that EGFR‐p62 pathway plays a critical role in Akt‐mediated positive regulation of autophagy.